2020
DOI: 10.1038/s41378-020-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, diamond-based microelectrodes fabricated using the diamond growth side for neural sensing

Abstract: Diamond possesses many favorable properties for biochemical sensors, including biocompatibility, chemical inertness, resistance to biofouling, an extremely wide potential window, and low double-layer capacitance. The hardness of diamond, however, has hindered its applications in neural implants due to the mechanical property mismatch between diamond and soft nervous tissues. Here, we present a flexible, diamond-based microelectrode probe consisting of multichannel boron-doped polycrystalline diamond (BDD) micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…The example shows an electrode array made of mechanically and chemically stable, boron-doped polycrystalline diamond (BDD) (upper). Morphological response of rat cortical neurons on the Parylene C and microcrystalline diamond (MCD) substrates (lower) appeared similarly to the control substrate (reprinted with permission from Fan et al, 2020 ). (D) Biodegradability and bioresorbability.…”
Section: Key Materials Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The example shows an electrode array made of mechanically and chemically stable, boron-doped polycrystalline diamond (BDD) (upper). Morphological response of rat cortical neurons on the Parylene C and microcrystalline diamond (MCD) substrates (lower) appeared similarly to the control substrate (reprinted with permission from Fan et al, 2020 ). (D) Biodegradability and bioresorbability.…”
Section: Key Materials Characteristicsmentioning
confidence: 99%
“…With large amounts of water in their structures, these materials are highly hydrated to increase the energetic penalty of removing water for protein and microorganism attachment. Engineered antifouling electrode materials, such as sp 3 carbon-enriched, boron-doped polycrystalline diamond (BDD), also show the advantages of improved biocompatibility and reduced biofouling compared to conventional electrode materials (Meijs et al, 2016 ; Fan et al, 2020 ), as shown in Figure 2C . Moreover, nanostructured surfaces with low friction and low surface energies can effectively decrease cell attachment onto the implant surface, and hence, reduce the possibility of biofouling formation (Chapman et al, 2017 ; Boehler et al, 2020 ).…”
Section: Key Materials Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows schematically these two typical fabrication methods for making all diamond microelectrode probes and MEAs. To further improve the mechanical flexibility, pre-patterned BDD MEAs can be transferred from a solid substrate onto a soft polymer substrate, such as polynorbornene [ 131 ], polyimide [ 132 ] and parylene C [ 133 , 134 ] to form BDD-on-polymer MEAs with reduced mechanical rigidity ( Figure 1 E [ 131 ] and Figure 1 F [ 133 ]). Recently, BDD paste electrodes suitable for electroanalytical applications have been reported by Kondo et al, offering a cheaper alternative to fabrication of flexible BDD MEAs [ 135 , 136 ] ( Figure 1 G [ 136 ]).…”
Section: Motivation For Diamond Sensors For Neurochemical Detectiomentioning
confidence: 99%
“…Surface fouling due to accumulation of oxidized products on the electrode surface further limits electrode selectivity and sensitivity in the long-term. While challenges exist, the inherent robustness, electrochemical stability, wide potential window, and good electrocatalytic activity of highly boron-doped polycrystalline or nanocrystalline diamond electrodes make these materials suitable candidates to detect DA [ 96 , 105 , 133 , 144 , 145 ], epinephrine (EP) [ 146 ], and NEP [ 147 , 148 ]. These electroactive NTs belong to the family of catecholamines (e.g., DA), which are readily oxidized to an ortho-quinone that can be electrochemically detected using pristine BDD electrodes without any surface modification or functionalization.…”
Section: Motivation For Diamond Sensors For Neurochemical Detectiomentioning
confidence: 99%